The financial potential assessment of corporate business (using the example of JSC «Dorspetsstroy» and JSC «DSU-7») - Kolomiytseva A. R. (Science in figures, 2018)
the article reviews the methodological aspects of financial potential assessment of corporate business. The author proposes a step-by-step methodology for its assessment by analyzing the factors affecting the magnitude of the financial potential. The author carries out financial potential assessment using the example of road construction corporations based on the proposed methodology.
Keywords: рентабельность; финансовый потенциал; оценка; ликвидность; финансовая устойчивость; profitability; liquidity; financial stability; корпоративный бизнес; financial potential; estimation; corporate business